(untitled) (Journal of the College of Basic Education, 2023)
Mannich bases have rececived great attention in recent years because of their proven antimalarial, antifungal and anticancer activities, coordination certain metal ions to them have interested use in synthesizing and studying structural aspects of metal complexes with oxygen and nitrogen donor ligands. The chelate ligand 4-hydroxy-3-(4’-morpholinyl methyl) quinoline was prepared by condensation of the formaldehyde with morpholine and 4- hydroxyquinoline in ethanol. A methanolic solution of the prepared ligand was reacted with a methanolic solution containing metal ions Fe (II), Co (II), Ni (II), Cu (II), Cd (II) to give metal complexes. The reaction of Fe (II), Co (II), Ni (II), Cd (II) ions with chelate ligand gave the mono-nuclear tetrahedral complexes, and mono-nuclear square planar complex with Cu (II). Their molecular structures were studied by FTIR, 1H-NMR and UV-Visible spectra, atomic absorption technique, elemental analysis have been performed using CHN, magnetic susceptibility and conductivity measurements.